A novel mutation in SMARCB1 associated with adult Coffin-Siris syndrome and meningioma - Guo Zhenglong; Bai Jie; Liu Yang; Zhang Xianwei; Yang Wenke; Wang Jinming; Zhang Yuwei; Xiao Hai; Hao Bingtao; Liao Shixiu (Acta Biochimica et Biophysica Sinica, 2024)
SMARCB1 encodes a core subunit of the SWI/SNF chromatin remodeling complex, which plays a crucial role in the regulation of gene expression. Germline mutations in the SMARCB1 gene have been linked to early childhood Coffin-Siris syndrome type 3 (CSS3), a rare congenital malformation syndrome characterized by severe developmental delay and intellectual disability. In this study, we report a family of two adult CSS3 patients with a novel missense SMARCB1 mutation (c.1091A>C, p.Lys364Thr) identified through whole-exome sequencing (WES). Both patients exhibit selective difficulties in verbal learning and experience language delays. Additionally, the development of meningioma is confirmed in one of the patients. Mechanistic studies suggest that this missense mutation may abnormally activate the MAPK signaling pathway, which is implicated in the pathogenesis of tumor progression and neurodevelopmental disorders. This is the first reported case of a germline mutation in the SMARCB1 gene associated with both CSS3 and meningioma, thereby expanding the phenotypic spectrum of SMARCB1-related disorders.